New computer program TecD for tectonomagmatic discrimination from discriminant function diagrams for basic and ultrabasic magmas and its application to ancient rocks. - Verma, S. P.; Rivera-Gómez, M. A. (Journal of Iberian Geology, 2013)
Due to the unavailability of suitable software, a new computer program TecD (Tectonomagmatic Discrimination) was written in Visual Basic for using four sets of new discriminant function based diagrams published during 2004-2011. This bilingual (both in English and Spanish) program evaluates igneous rock geochemistry data in 20 different multi-dimensional diagrams (4 sets of 5 diagrams each), automatically counts the number of samples plotting in different tectonic fields, computes success rates (%) for a given area or set of rock samples, provides scalable vector diagrams that can be opened and modified in different commercial software, and presents a synthesis of this application in a final report. Three examples are presented to highlight the use of TecD. Ocean island setting is inferred for 56 Ma basic rocks from Faroe Islands (Atlantic Ocean), mid-ocean ridge for 2700 Ma Archean Abitibi greenstone belt (Canada), and arc setting for 2950 Ma Mallina basin (Australia). Additional criteria for the interpretation of these diagrams are also briefly discussed.